Growth, morphology, assimilate partition and dry matter production in Phaseolus vulgaris L. - Costa, Roberto C.L; Lopes, Nei Fernandes; Oliva, Marco A. (Pesquisa Agropecuaria Brasileira, 1991)
Growth, morphology, assimilate partition and dry matter production were studied in Phaseolus vulgaris L. cv. ’Negrito 897’ in greenhouse, under three nitrogen levels (50, 125 and 200 ppm of N) and two water systems, field capacity (≈ -0.03 MPa) and cyclic water stress (-0.03 to -1.0 MPa). Water deficit reduced the plant height, the leaflet number, the leaf area and the yield components but this effect was partially minimized by high nitrogen levels. The water deficit reduced the rates of dry mater production of all plant organs. In well watered plants, nitrogen had a great effect on organs growth rate, mainly on pods. On the other hand, in plants under water stress, N affected the assimilate accumulation only in the reproductive phase. Seed dry matter increased until final harvest in all treatments probably because seeds received assimilates from other organs at this time. The pericarps dry matter diminished at final harvest, independently of water system and nitrogen level, showing that assimilates were translocated from pericarp to seeds. The water system showed greater effect on assimilate partition than nitrogen levels. However, high N levels had a tendency to minimize the water stress effects.